PERAN STRATEGIS KEMITRAAN BUMDES DALAM PEMBANGUNAN DESA BERKELANJUTAN DI INDONESIA - Kreshna Reza, Heru; Judijanto, Loso; Susanti, Melly; Vanny Varera, Restyan (Creative Research Management Journal, 2025)
This research aims to evaluate the role of Village-Owned Enterprises (BUMDes) in supporting village economic independence, improving community welfare, and achieving Sustainable Development Goals (SDGs). Descriptive qualitative method, using instruments of in-depth interviews, observation, and document analysis. The sampling technique used was purposive sampling, focusing on BUMDes in Bengkulu Province. The research shows that BUMDes has succeeded in increasing village income by around 20% in the last two years. In addition, the BUMDes programme also encourages sustainable natural resource management, creates new jobs, and improves the capacity of village communities in managing businesses. 70% of villages involved in the strategic partnership have implemented new technologies that focus on agricultural and natural resource efficiency. This research is limited to BUMDes in Bengkulu Province, so it cannot describe the overall dynamics of BUMDes in Indonesia. This research can significantly contribute to the development of village development policies, community empowerment, as well as the implementation of SDGs at the village level, with a focus on sustainable natural resource management and local economic improvement through BUMDes.